Middle Level Education Aims for Equity and Inclusion, but Do Our School Websites Meet ADA Compliance? - John A Huss (Middle Grades Review, 2019)
An often-overlooked component of a middle school website is the necessity for that website to be accessible to those with disabilities, while following the guidelines of the Americans with Disabilities Act (ADA) and Section 508 of the Workforce Rehabilitation Act. In support of the belief that support the belief that inclusive education and respect for diversity should be integrated throughout the school, this study investigated the accessibility of middle school websites in Indiana, Kentucky, and Ohio by selecting a random sample of 150 schools and analyzing their homepages using WAVE (Web Accessibility Versatile Evaluator), which reports accessibility violations by annotating a copy of the page that was evaluated and presenting embedded icons and indicators to disclose breaches with ADA. Out of 150 districts, 54% had errors that need immediate attention and all 150 schools had alerts of likely violations that ranged from alt-text omissions and empty or confusing links to issues with color contrast and keyboard-only navigation. The article proceeds to give practical suggestions for eliminating many of the errors, even for those shareholders with less than sophisticated technological expertise.
Keywords: Websites; accessibility; disabilities; middle level education